Shoppers satisfaction and revisit intention based on attributes of shopping experiences / Khairul Afifah Mohd Kamaluddin, Shahrul Nizam Ismail and Shamimi Mohd Isa - Mohd Kamaluddin, Khairul Afifah; Ismail, Shahrul Nizam; Mohd Isa, Shamimi (2014)
The study purpose is to identify the Tourists Shopping Satisfaction Based on Shopper Attributes and Shopping Experiences in Malacca. It is compulsory to know the factors that influence tourist’s satisfaction to do shopping activities in Malacca. For this study, the researcher chooses three determinants of shopping experiences which are venue environment and services, merchandise value and staff service quality. There are 91 respondents were chosen consist of tourists that come in Malacca and residents in three areas of shopping mall in Malacca which are Dataran Pahlawan Mall, Mahkota Parade and Jusco Mall in Malacca city. The findings of the study show that venue environment and services, merchandise value and staff service quality have significant relationship with tourists' satisfaction in Malacca. Based on the results, the researcher found that the most significant determinant that influenced tourist’s satisfaction in Malacca to go abroad is staff service quality.